Workshop on Digital Marketing and Plastic Waste Treatment Training in Menguri, Hargotirto, Kokap, Kulon Progo - Datuk Mahmud; Riza Wahyu Kurnia; Abdul Jawad; Ravindra Luqman; Vicky Victoriany; Lathifah Lathifah; Niken Uswah; Atika Zulfi; Catur Setioningsih; Aisya Rahma (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2019)
Nowadays, technology on communication was widely used in order to support various enterprises. Based on this statement, we are interested to give wokshop about digital marketing in Menguri. Based on the location survey, Menguri is potential in brown sugar production, vegetable farming, and rabbit farming that held by Sarwodadi Women Farmer Group. Digital marketing training was held to introduce how to market their product using Android technology considering that most of the people of Menguri were using an Android-based mobile phone. Besides that, most of them were using polybag that made of plastic to plant a vegetable. So it is important to educate and train them on plastic waste treatment. The Interactive dialogue method was used at the digital marketing wokshop and plastic waste treatment training. That wokshop and training were purposed to gain knowledge and skills to develop their enterprises. The results of this wokshop and training are gaining in knowledge and skill of Dusun Menguri social community.